A segmentation study of cinema consumers based on values and lifestyle. (March 2018) - Díaz, Asunción; Gómez, Mar; Molina, Arturo; Santos, Jesús
Abstract: The objective of this study is to analyse the segments of cinemagoers in a shopping centre based on their values ​​and lifestyle. Hierarchical segmentation techniques are used to identify different groups of consumers. Specifically, four segments are obtained from a sample of 391 participants, and the variation among the segments in the frequency of leisure activities in the shopping centre is analysed. The results contribute to the body of theoretical and empirical literature regarding the segmentation of customers at shopping centres. The conclusions and recommendations for managers of shopping centres highlight the importance of executing different strategies for each segment.